PTU-159 Variable Utility Of Chromogranin A Assays In The Diagnosis Of Gastric Carcinoid Type 1. (9th June 2014) - Rossi, RE; Martin, NG; Garcia-Hernandez, J; Mandair, D; Mullan, M; Toumpanakis, C; Caplin, ME
Abstract : Introduction: Chromogranin A (CgA) is used in the diagnosis and follow-up of patients with neuroendocrine tumours, whilst there is debate over the accuracy of CgA assays in gastric carcinoid type 1 (GC1). Clinical interpretation of CgA results may be affected by the heterogeneity between available assays. The commercial CgA assay, DAKO (DAKO, Denmark A/S, Glostrup, Denmark) is an ELISA which recognises a 23 kD C terminal fragment of CgA; the Imperial Supra-regional Assay Service radioimmunoassay (SAS Hammersmith Hospital, Imperial College, London) is a competitive radioimmunoassay raised against the whole pancreastatin molecule. Present study is aimed at comparing CgA-DAKO and CgA-SAS to determine their accuracy in the diagnosis of GC1. Methods: Patients with a confirmed diagnosis of GC1 and available plasma CgA measurements according to two different assays (SAS, DAKO) were included and retrospectively reviewed. CgA values were ranked in 4 groups: 1. normal values, 2. increase <2 upper limit of normal (ULN), 3.increase between 2–5 ULN, 4. increase >5 ULN. Results: 26 patients, 17 female and 9 male, mean age 55 years ± 11.75, were identified. At diagnosis, median CgA-DAKO were significantly higher than median CgA-SAS (81, normal range <27 IU/l versus 34.5 pmol/l, normal range <60 pmol/l, T=35.5, p < 0.001). When ranking the data, the results confirmed median CgA-DAKO significantly higher than median CgA-SAS: 3 vs. 1, T=0, p < 0.001. Sensitivity was 77% and 7.7% for CgA-DAKO and CgA-SAS, respectively. Conclusion: CgA-DAKO shows a better sensitivity than CgA-SAS for the diagnosis of GC1. Accurate diagnostic biomarkers may identify those patients who may benefit from a closer endoscopic follow-up in cases of raised neuroendocrine markers. Further prospective studies are needed highlighting the difference in diagnostic sensitivity between assays. References: Ramachandran R, et al . Improved diagnostic accuracy for neuroendocrine neoplasms using two chromogranin A assays. Clin Endocrinol (Oxf). 2012;76: 831–836 Baudin E, et al . Impact of chromogranin-A measurement in the work-up of neuroendocrine tumors. Ann Oncol 2001;12(Suppl 2): S79–S82 Stridsberg M, et al . A comparison between three commercial kits for chromogranin A measurements. Journal of Endocrinology 2003:177:337–341 Ardill JES. Circulating markers for endocrine tumours of the gastroenteropancreatic tract. Annals of Clinical Biochemistry 2008:45, 539–559 Disclosure of Interest: None Declared.